Analisis Tingkat Kesulitan Soal Pemecahan Masalah Dalam Buku Siswa Pelajaran Matematika Wajib SMA Kelas XI Kurikulum 2013 - SELLA PUTRI ROSSALINI, DONNA; , Idris Harta, M.A., Ph. D (2017)
This study aims to analyze and describe the level of difficulty of problem solving items in the textbook of mathematics students of compulsory for high school grade XI curriculum 2013 based on the components of problem solving items include that types of problem, the types of number, the types of operation, amount operations, amount questions, the adequacy of data, and like-before questions. This research was qualitative. The object of this study is the textbook of mathematics students of compulsory for high school grade XI curriculum 2013 for and semester in 2014 published by the Ministry of Education and Culture. Questions analyzed include problem solving items in the problems, examples, exercises, and competence test. Data accumulation techniques by observation on the sample of every questions. Data analysis techniques are data reduction, data presentation, and conclusion. The result of this research showed that problem solving items in mathematics textbook required for high school grade XI curriculum 2013 when viewed from the types of operation, amount of operations, and the like-before problems is problem with high difficulty level; In terms of the adequacy of the data including problem with medium difficulty; And when viewed from the types of question, the types of number, and amount questions including problem with low difficulty level.